Amorphous colloidal photonic crystals assembled by mesoporous silica particles for thin layer chromatography with high separation efficiency and colorimetric recognition. Issue 48 (20th November 2020) - Zhang, Xin; Ran, Yumei; Fu, Qianqian; Ge, Jianping
Abstract : A mesoporous SiO2 amorphous photonic crystal film was used to develop new thin-layer chromatography with high separation efficiency and simplified recognition. Abstract : Amorphous photonic crystals (APCs) assembled by mesoporous SiO2 particles were first used to develop thin layer chromatography (TLC) with high separation efficiency and convenient colorimetric recognition. The m-SiO2 APC film has a large number of micron-scale pores, which significantly accelerate the solvent diffusion and address the problem of the short-distance development. Meanwhile, the abundant mesopores in m-SiO2 particles intensify the adsorption–desorption between analytes and APC film. Although the critical micron-scale pores were introduced by the sacrifice of long-range ordered structure, the APC film still has uniform structural colors due to its short-range ordered structure. Therefore, the APC film retains the advantage of colorimetric recognition, where the loaded chemicals cause an increased refractive index and a structural-color change. Compared to traditional SiO2 gel TLC, the sample recognition in APC TLC was simplified because chemical compounds, which must be dyed, can be directly recognized now. Meanwhile, the separation resolution achieved by m-SiO2 APC TLC was also improved due to the enhancement of adsorption–desorption.